Nuclear receptor co-activator 4 interacts with RUVBL1/2 to maintain genome integrity through double-strand break repair - Yingying Chen; Qi Zhang; Zongjian Tao; Shaoting Lv; Cheng Quan; Gangqiao Zhou; Hongxia Chen (DNA Repair, 2026)

Functions of the transcription factor myb-like in sex determination and differentiation in Portunus trituberculatus - Shaoting Jia; Weikang Lan; Yuchao Huang; Yichen Su; Baoquan Gao; Ping Liu; Jianjian Lv (Aquaculture, 2025)

Comparative transcriptomic analysis and validation of the ovary and testis in the ridgetail white prawn (Exopalaemon carinicauda) - Shaoting Jia; Ling Jin; Jianjian Lv; Jiajia Wang; Jitao Li; Ping Liu; Jian Li (Frontiers in Marine Science, 2022)
The ridgetail white prawn, Exopalaemon carinicauda is an important cultured seawater species in China. As female E.carinicauda grows faster than males, it is significant to search for the differentially expressed genes (DEGs) between males and females. However, there is no public available E.carinicauda genome data, and genes related to E. carinicauda sex differences are unclear. In this study, the transcriptome sequencing for ovary and testis tissues of E. carinicauda were conducted, and 20,891 DEGs were identified including 11,709 up-regulated DEGs and 9,182 downregulated DEGs. The functional categories related to meiosis and reproduction were enriched as well as the steroidogenesis KEGG pathway was clustered. Furthermore, the genes related to male reproduction and cell cycle were dug out which were verified by real-time PCR. In addition, two-color fluorescent in situ hybridization result showed that foxj1b might play roles during early stage of the ovary development. Therefore, our result provides clues for the study of genes related to reproduction and sex difference in E.carinicauda .

Evidences of Z- and W-Linked Regions on the Genome of Fenneropenaeus chinensis - Qiong Wang; Jianjian Lv; Xianyun Ren; Jiajia Wang; Shaoting Jia; Yuying He; Jian Li (Frontiers in Marine Science, 2021)
Fenneropenaeus chinensis is a commercially cultured shrimp in China. F. chinensis adults show significant sexual dimorphism, with larger females than males. However, sex determination (SD) of F. chinensis has not yet been elucidated. Clarification of the sex-determining system of F. chinensis could enrich our knowledge of the sex differentiation mechanism in crustaceans and facilitate the study of sex-controlling technologies. Here, we studied the sex-determining system of F. chinensis using the fixation index ( F ST ) between the sexes to detect the genetic differentiation in resequencing data of multiple males and females. We located the candidate sex chromosome in the genome of F. chinensis and concluded the female heterogametic (ZW) SD system. We also assembled female-specific sequences, which could be used as molecular markers to identify the sex of F. chinensis . However, the differentiation of the F. chinensis Z and W chromosome is limited. RNA-seq data detected many genes with male-biased expression in the Z-specific region, which possibly could further intensify the divergency between the Z and W chromosomes.